2001
DOI: 10.1017/s0003055400400134
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of the Vanishing Voter

Abstract: The apparent decline in voter participation in national elections since 1972 is an illusion created by using the Bureau of the Census estimate of the voting-age population as the denominator of the turnout rate. We construct a more accurate estimate of those eligible to vote, from 1948–2000, using government statistical series to adjust for ineligible but included groups, such as noncitizens and felons, and eligible but excluded groups, such as overseas citizens. We show that the ineligible population, not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
186
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(188 citation statements)
references
References 14 publications
(28 reference statements)
1
186
0
1
Order By: Relevance
“…7. McDonald and Popkin (2001) found that when this difference is taken into account, the trend in turnout is higher than it may appear. The scope of this study does not permit me to seek out each district's voting eligible population.…”
Section: Discussionmentioning
confidence: 94%
“…7. McDonald and Popkin (2001) found that when this difference is taken into account, the trend in turnout is higher than it may appear. The scope of this study does not permit me to seek out each district's voting eligible population.…”
Section: Discussionmentioning
confidence: 94%
“…Figure 1 plots the percentage of children in single parent households because of divorce against youth turnout rates based on the eligible electorate (as computed by McDonald and Popkin, 2001). The figure shows that divorce rates rose steadily until 1992 and that (with large idiosyncratic shocks) turnout shows a general downward trend through 1996 (we expect a lag because the children represented by the lower line in the figure are not yet eligible to vote).…”
mentioning
confidence: 99%
“…Variation is potentially large across states, because each state is guaranteed at least one congressional district regardless of state population, and states have different rules for determining eligibility to vote (e.g., voting rights of convicted felons). We recognize a distinction between voting-eligible population (VEP) and voting-age population (VAP); see McDonald and Popkin (2001). District-level figures for VEP are not available, but can be estimated dividing the state-level VEP figures by the number of congressional districts in the state.…”
Section: Survey and Critiquementioning
confidence: 99%